Manajemen Intensif Peripartum pada Pasien COVID-19 - Apsari, Ratih Kumala Fajar; Wisudarti, Calcarina Fitriani Retno; Negara, Adista Yugadhyaksa Gupta (Jurnal Komplikasi Anestesi, 2021)
COVID-19 is an infectious disease caused by the SARS-CoV-2 virus. Pregnant women in the third trimester and after delivery are at risk for severe COVID19. Intensive management of pregnant women with COVID-19 consists of a variety of steps. Key points of intensive management include fluid management, steroids, thromboprophylaxis, antibiotics, monoclonal antibodies, and ventilation management. Laboratory, radiological, and clinical examination monitoring should be carried out as needed. In pregnant women with severe COVID-19, there are critical targets that must be achieved. Patient management must be adjusted to achieve these targets. This case report discusses a 23-year-old woman who was 30 weeks pregnant who experienced severe COVID-19 and eventually died. There is much to be learned about the intensive management of pregnant women with COVID19 from this case.